PENGARUH GAYA MENGAJAR GURU TERHADAP MINAT BELAJAR IPS SISWA - Eti Muliani; Juwita Tindaon (EJoES (Educational Journal of Elementary School), 2021)
This study aims: (1) To describe the teaching style of teachers in social studies subject for class V at Binjai State Islamic Senior High School, Academic Year 2020/2021. (2) To find out a description of student interest in learning in social studies subject for class V at Binjai state madrasah ibtidaiah for the academic year 2020/2021. (3) To find out whether there is a significant influence between teacher teaching styles on student interest in learning in class social studies subjects at Binjai state madrasah ibtidaiah for the 2020/2021 academic year. The results of this study are: (1). The description of the Teacher's Teaching Style is 60.47 which is categorized as quite good. (2). Description of Student Interest in Student's Social Studies Student's Eyes is 73.44 which is in the good category. (3).There is a significant influence between the Teaching Style of the Teacher and the Student's Learning Interest in the Social Sciences Subject of Class V Madrasah Ibtidaiah Binjai in the Learning Year 2020/2021.